Analisis Kelayakan Usaha Makanan Ringan Berbasis Produk Lokal: Studi Empiris UMKM - Harjun Harjun; Dila Lestari (Edupreneurship: Jurnal Pendidikan Ekonomi, 2026)
Local product-based snack food businesses experience rapid growth in urban areas as response to changing consumer preferences toward authentic, affordable, and sustainable products. This research analyzes feasibility of local snack food businesses in Lorong Pelangi area through empirical approach integrating field observation, in-depth interviews, and structured questionnaires. Three snack food UMKMs become investigation objects: Kios Aneka Kue (revenue Rp11 million/3 months), Warung Pisang Enak (revenue Rp10 million/3 months), and Warung Sakinah (revenue Rp20 million/3 months), with total fifteen consumer respondents. Mixed methods methodology combines operational condition observation, semi-structured interviews with owners/employees to explore strategic dimensions and operational challenges, and questionnaires with categorical rating scales (Sangat Baik, Baik, Kurang Baik, Tidak Baik) to measure consumer satisfaction. Results demonstrate that snack food businesses in this area possess substantial feasibility with stable consumer demand (2-3 purchases/week), affordable average expenditure (Rp5,000-Rp15,000/visit), and high satisfaction levels. Warung Sakinah recorded highest revenue through combination of strategic location, consistent product quality, and effective offline service delivery, despite not yet utilizing digital marketing. Warung Pisang Enak demonstrates modern adaptation with active digital marketing strategy (Instagram, TikTok, celebrity endorsement), while Kios Aneka Kue still relies on traditional word-of-mouth. Dominant purchase decision factors include product taste, affordable pricing, and strategic location. Challenges include intense competition, trend volatility, and necessity for continuous innovation. In conclusion, all three UMKMs demonstrate good business viability with recommendations including digital marketing intensification, systematic quality control, regular consumer feedback integration, and strategic product differentiation for long-term sustainable growth.